2011
DOI: 10.1021/jp2056688
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effects of PdO Species on CO Oxidation over PdO–CeO2 Catalysts

Abstract: The PdO/Ce1–x Pd x O2−δ catalyst prepared by a solution-combustion method contained free surface PdO species and PdO species in Ce1–x Pd x O2−δ solid solution, whereas the PdO/CeO2 catalyst prepared by an impregnation method contained only free surface PdO species. The free surface PdO species could be removed by nitric acid. Contributions of the PdO species to catalytic CO oxidation were quantitatively evaluated. The free surface PdO species in the PdO/Ce1–x Pd x O2−δ catalyst had the highest activity (969.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 51 publications
10
93
0
1
Order By: Relevance
“…Most of the Pt 2+ species are embedded in CeO 2 matrix due to the formation of Pt-Ce-O solid solution, which makes the CO molecules not accessible to these species. Similar findings were also reported in PdO/CeO 2 [39] and CuO/CeO 2 [23] catalysts. For example, Meng et al [39] reported CO chemisorption on a PdO/CeO 2 catalyst; however, there is no CO chemisorption on the catalyst when the surface Pd species were removed by a nitric acid treatment even though oxidized Pd species were detected in the catalyst (in form of Pd-Ce-O solid solution).…”
Section: Characterizations Of Pt/ceo 2 Catalystssupporting
confidence: 89%
See 2 more Smart Citations
“…Most of the Pt 2+ species are embedded in CeO 2 matrix due to the formation of Pt-Ce-O solid solution, which makes the CO molecules not accessible to these species. Similar findings were also reported in PdO/CeO 2 [39] and CuO/CeO 2 [23] catalysts. For example, Meng et al [39] reported CO chemisorption on a PdO/CeO 2 catalyst; however, there is no CO chemisorption on the catalyst when the surface Pd species were removed by a nitric acid treatment even though oxidized Pd species were detected in the catalyst (in form of Pd-Ce-O solid solution).…”
Section: Characterizations Of Pt/ceo 2 Catalystssupporting
confidence: 89%
“…Similar findings were also reported in PdO/CeO 2 [39] and CuO/CeO 2 [23] catalysts. For example, Meng et al [39] reported CO chemisorption on a PdO/CeO 2 catalyst; however, there is no CO chemisorption on the catalyst when the surface Pd species were removed by a nitric acid treatment even though oxidized Pd species were detected in the catalyst (in form of Pd-Ce-O solid solution). Thus, in the current case we believe that the CO chemisorption on the Pt/CeO 2 catalysts mainly takes place on the surface metallic Pt species (as the catalysts were pre-reduced in H 2 ) but the oxidized Pt species are not accessible for the CO molecules.…”
Section: Characterizations Of Pt/ceo 2 Catalystssupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, noble metal incorporated perovskites represent a valuable alternative as catalysts since they have a high thermal stability and their elevated compositional flexibility along with the presence of chemically active structural defects and localized electronic states offer tremendous tailoring possibilities for designing more efficient catalytic processes. 8,20,21 Palladium oxides is one of the most useful catalyst in oxidation reaction 22,23 and the incorporation of Pd in perovskite structure turned out to efficiently suppress the inconvenient clustering of Pd particles, thereby improving the catalytic activity.…”
mentioning
confidence: 99%
“…Previous studies on Pd-CeO 2 catalysts were usually calcined at temperatures below 600°C and CO oxidation performance was used as conventional indicator for evaluating the degree of metal-support interaction [21]. When supported Pd-Ce oxides are thermally treated at higher temperatures, the activity is generally considered to decrease to some content due to aggregation of Pd or sintering of supports [22].…”
Section: Introductionmentioning
confidence: 99%